PENGARUH KUAT SINYAL INTERNET 3G OPERATOR THREE TERHADAP PERANGKAT PENERIMA DI KHATULISTIWA PLAZA - Penianto . (Faculty of Engineering, Universitas Tanjungpura, 2016)
ABSTRACT- In the 3G communication network for the operator Three, there are locations where 3G internet signals received less than the maximum in its Internet services, so that conducted this study to determine the cause of less maximal 3G internet service provider in the Area Three Khatulistiwa Plaza. The study consisted of RSCP calculation using the model Cost-231 Hatta. Measurement RSCP, Ec/No, and use the Walk Test Throughput. Calculations and measurements are divided into 2 of the calculations and measurements before and after you install repeaters installed repeaters. The purpose of the installation of the repeater is to amplify the signal, in order to obtain a better signal. The result of the calculation before and after you install repeaters indicates the received signal power level is in the range of 0 to -74, this indicates the received signal quality is very good by the standards of operator Three, as well as measurement results before and after you install repeaters indicates the level of signal strength is above the acceptable standard of operator Three, the standard lowest signal RSCP for Three operators are in the range of - 86 to -90. 3G network for data quality before and after you install repeater is below the standard of operator Three, the standard lowest signal Ec/No to Three operators are in the range of -8 to -12. For repeater is used on the Khatulistiwa Plaza does not affect the measurement of RSCP and Ec/No, only affect the measurement throughput, this indicates that the repeater does not work optimally, based on the results of the analysis of this is because the repeater is used Repeater RD-1840 works at a frequency of GSM1800 MHz, while the frequency of the transmitter Node B to the 3G network is 2100 MHz, it is recommended that you should use the repeater SP- 2110, SP-2100 because the repeater is working on WCDMA2100 MHz frequency. Keywords: Strong signals, 3G, RSCP, Ec/No, Throughput.